Introducing the ArsR-Regulated Arsenic Stimulon - Rawle, Rachel; Saley, Tara C.; Kang, Yoon-Suk; Wang, Qian; Walk, Seth; Bothner, Brian; McDermott, Timothy R. (Frontiers in Microbiology, 2021)
The microbial ars operon encodes the primary bacterial defense response to the environmental toxicant, arsenic. An important component of this operon is the arsR gene, which encodes ArsR, a member of the family of proteins categorized as DNA-binding transcriptional repressors. As currently documented, ArsR regulates its own expression as well as other genes in the same ars operon. This study examined the roles of four ArsR proteins in the well-developed model Gram negative bacterium Agrobacterium tumefaciens 5A. RNASeq was used to compare and characterize gene expression profiles in +/- arsenite treated cells of the wild type strain and in four different arsR mutants. We report that ArsR-controlled transcription regulation is truly global, extending well beyond the current ars operon model and includes both repression as well as apparent activation effects. Many cellular functions are significantly influenced, including arsenic resistance, phosphate acquisition/metabolism, sugar transport, chemotaxis, copper tolerance, iron homeostasis, and many others. While there is evidence of some regulatory overlap, each ArsR exhibits its own regulatory profile. Furthermore, evidence of a regulatory hierarchy was observed; i.e. ArsR1 represses arsR4; ArsR4 activates arsR2, and ArsR2 represses arsR3. Additionally and unexpectedly, aioB (arsenite oxidase small subunit) expression was shown to be under partial positive control by ArsR2 and ArsR4. Summarizing, this study demonstrates the regulatory portfolio of arsenite-activated ArsR proteins includes essentially all major cellular functions. The broad bandwidth of arsenic effects on microbial metabolism assists in explaining and understanding the full impact of arsenic in natural ecosystems, including the mammalian gut.